Nurses: a guide towards assistive devices and technologies for the visually impaired individuals - Yadav, Nisha; Rawat, Bhim S.; Saini, Sushma K.; Pandav, Surinder S.; Raj, Srishti; Duggal, Mona (International Journal Of Community Medicine And Public Health, 2023)
Assistive devices for people with visual disability is growing rapidly over the past few years around the world. These devices enhance the functioning and performance of daily living skills, thereby improves the independent living and quality of life of these individuals. These innovations range from low to high cost and it includes devices which assist the visually impaired individual in mobility, reading, writing, daily living, and communication technologies. Children primarily need these devices for education whereas adults use these devices for doing daily routine tasks. It is expected that the need and demand of these devices and technologies will increase over time due to the exceptional growth in the proportion of population with visual impairment, specifically in low middle-income countries like India. Therefore, the first and forefront strategy is to introduce assistive devices to the visually impaired individuals and create awareness, sensitize eye care professionals, potential beneficiaries, caregivers, and their families. The present paper will highlight some of the assistive devices and technologies which will increase the independence in doing activities of daily living as well as increase the quality of life of individuals suffering from visual impairment.